2012
DOI: 10.1021/la300850g
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface Influence on the Structure of Protein Adsorbates as Revealed by in Situ X-ray Reflectivity

Abstract: The adsorption process of proteins to surfaces is governed by the mutual interactions among proteins, the solution, and the substrate. Interactions arising from the substrate are usually attributed to the uppermost atomic layer. This actual surface defines the surface chemistry and hence steric and electrostatic interactions. For a comprehensive understanding, however, the interactions arising from the bulk material also have to be considered. Our protein adsorption experiments with globular proteins (α-amylas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 66 publications
3
34
0
Order By: Relevance
“…Recently, a similar influence was detected on the adsorption kinetics of proteins [11][12][13] and the adhesion of bacteria [14]. These experiments used materials whose contribution to the potential had been tuned by means of surface stratification.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Recently, a similar influence was detected on the adsorption kinetics of proteins [11][12][13] and the adhesion of bacteria [14]. These experiments used materials whose contribution to the potential had been tuned by means of surface stratification.…”
Section: Introductionmentioning
confidence: 66%
“…All wafer types were characterized using atomic force microscopy, ellipsometry and water contact angle measurements (cf. table 2; further characterization data available in [13,34]). Immediately prior to the experiments, the substrates were cleaned by immersing them subsequently into ethanol and acetone (5 min each) in a ultrasonic bath and rinsing them for 30 min in boiling DI water.…”
Section: Preparation and Cleaning Of Substratesmentioning
confidence: 99%
“…The influence of van der Waals interactions from the bulk material to the top surface can be also transferred to the contact angle information, since van der Waals forces range over tens of nanometers [23]. Hähl et al [24] studied the adsorbed layer of globular proteins on silicon wafers with silicon oxide layers of different thickness. They proved that the characteristics of the adsorbed layers of proteins were affected not only by a few top layers of atoms on the surface, but also were sensitive to the van der Waals forces from the subsurface layers.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Evers et al shows a change of the denaturation of lysozyme with salt concentration leading to an improvement of the adsorption at high salt concentration [53]. Hahl et al [54] have also shown by X-ray reflectivity that, at low concentration (0.1 mg/ml), a-amylase, bovin serum albumin (BSA) and lysozyme are denaturated on hydrophobic surfaces and not denaturated on hydrophilic SiO 2 . Lu et al [41] also studied lysozyme adsorption on OTS as function of pH at a low protein concentration of 0.03 mg/ml.…”
Section: Ps1 Ps001mentioning
confidence: 99%